Through the Looking Glass: A Reconstructive Architecture for Machine Access Consciousness - Hsing, Nicole (Proceedings of the AAAI Symposium Series, 2026)
Theories of access consciousness predict specificarchitectural signatures: parallel specialized processing,synthesis into a unified representation, and globalavailability for reasoning and action. We present MIRROR, acognitive architecture that implements these features inlarge language models and tests whether they produce thefunctional behaviors these theories predict.MIRROR separates immediate response generation fromasynchronous deliberative processing through twocomponents: an Inner Monologue Manager that generatesparallel cognitive threads (tracking goals, reasoning, andmemory simultaneously), and a Cognitive Controller thatsynthesizes these threads into a bounded first-personnarrative. Critically, this narrative is not accumulatedbut reconstructed each turn—mirroring the reconstructivenature of human episodic memory, where the self-model iscontinuously rebuilt rather than retrieved. The resultingrepresentation functions as an episodic buffer: alimited-capacity workspace where information from parallelprocesses becomes globally available for downstreamreasoning.We evaluated MIRROR on multi-turn dialogue requiringretention of personal safety constraints amid competingsocial demands—a task requiring relevant context to remainaccessible across conversational turns despite distraction.MIRROR-augmented models achieve 21% average improvementover baselines, with the key finding being not themagnitude but the pattern: performance gains concentrate inscenarios requiring integration of temporally distantinformation under social pressure, precisely where accessconsciousness theories predict global availability providesadvantage.These results offer three contributions to machineconsciousness research: (1) a concrete implementation ofarchitectural features derived from consciousness theories,(2) empirical evidence that these features producepredicted functional signatures, and (3) an interpretablesystem where internal states can be inspected. Note: We donot claim MIRROR is conscious; we claim it provides atestbed where theoretical predictions can be tested andexamined.